Training in Writing Popular Scientific Articles to Improve Scientific Writing Abilities of Students of S1 Educational Administration Study Program - Samsilayurni, Samsilayurni; Agustina, Mediarita; Dewi, Nurmala (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
The skill of writing scientific papers has become a requirement for students as undergraduate graduates. The aim of this community service is to improve students' skills in writing articles as scientific papers. This research is classified as a case study in the form of training in writing popular scientific articles as a reference for students of the Educational Administration study program in semesters I (one), III (three) and V (five). Held on October 18, 2024, 40 (Forty) students registered as participants in the Popular Article Writing Training to Improve Scientific Writing Skills using lecture, discussion, example and practice methods. The evaluation results showed a significant improvement in students' writing skills, as seen from their ability to compose more structured and logical articles with a score of 87%. The support and guidance from lecturers and facilitators during the training greatly helped students in completing their writing so that they were more confident with a score of 85%. It is recommended that training be held periodically, guidance from lecturers be strengthened, and collaboration with scientific journals be expanded. Continuous evaluation is also necessary to ensure program effectiveness and necessary improvements. It is hoped that this activity can continue to be developed to provide greater benefits for students in improving the quality of their scientific work.